MULTI-STREAM ORIENTATION AND POSITION BASED ADAPTIVE GRAPH CONVOLUTIONAL NETWORK FOR SKELETON BASED ACTIVITY RECOGNITION - Tangirbergenov, Chingizkhan (Nazarbayev University School of Engineering and Digital Sciences, 2021)
Human activity recognition is an active research topic in the field of computer vision. The use of human action recognition is increasing day by day for surveillance, smart house and healthcare purposes. In general, human action recognition can be recognized from multiple modalities such as appearance (RGB images), depth, optical flow, body skeleton and etc. The main advantage of the skeleton data over other modalities is that it is resistant to changes in motion speeds, body scales, camera viewpoints and backgrounds interference. For that reason, in this paper, I focus on skeleton-based activity recognition. Starting with ST-GCN, graph convolutional networks (GCNs), that model the body skeleton data as spatiotemporal graphs, have reached good achievement in skeleton-based action recognition. However, in existing GCN based models, authors pay attention only to the XYZ coordinates of the bones and joints. In my model, apart from XYZ coordinates, information of joint orientations in terms of quaternions is used. Finally, the CNN model is used as a late fusion method to combine the results of all models. Extensive experiments on a state-of-the-art dataset called NTU-RGBD demonstrate that the performance of the proposed model can compete with state-of-the-art models.
Keywords: Type of access: Gated Access; NTU-RGBD; RGB